Aortic aneurysm – current state of knowledge analysis - Kruczek, Wiktor; Jelonek, Barbara; Durlak, Julia (Quality in Sport, 2025)
Introduction: Thoracoabdominal aortic aneurysms (TAAAs) are rare vascular pathologies involving the aorta from the descending thoracic to the abdominal segments. Due to their asymptomatic progression and high risk of rupture, they present significant diagnostic and therapeutic challenges. Although endovascular repair has become increasingly common, open surgical repair remains essential for complex or extensive aneurysms. Aim of the study: This study aims to summarize current knowledge on the etiology, classification, diagnosis, and classical surgical treatment of TAAAs. Materials and methods: A literature review was conducted focusing on diagnostic modalities, surgical techniques, and clinical outcomes. Special emphasis was placed on Crawford’s classification and protective measures during open repair. Results: TAAAs represent ~3% of all aortic aneurysms. Risk of rupture rises significantly with diameter, exceeding 14% annually for aneurysms >6 cm. CT angiography remains the diagnostic gold standard. Point-of-care ultrasound and MRI are useful adjuncts. Open surgery, although technically demanding, remains essential for extensive disease. Perioperative complications include spinal cord injury and renal failure. Techniques such as cerebrospinal fluid drainage and left heart bypass improve safety and outcomes. Conclusion: Open repair of TAAAs remains a key therapeutic approach. Early detection, optimal imaging, and tailored intraoperative strategies are essential to reduce complications and improve prognosis.